The effectiveness of promotion by Bumiputera entrepreneur development for Bumiputera wood-based products / Rahiza Rehan Che Rahim - Che Rahim, Rahiza Rehan (Faculty of Business and Management, 2006)
The Malaysian Timber Industry Board (MTIB) is a statutory body which governs the wood-based industry in this country. Among the many activities done by this body is to enhance and develop the wood-based sector. There is a department under MTIB specifically known as Bumiputera Entrepreneur Development / Pembangunan Usahawan Bumiputera (PUB) which task is to assist the Bumiputera Wood-Based Industry. This study is on the effectiveness of promotion by the PUB for the Bumiputera wood-based products. The promotions carried out were mainly the exhibitions held and the promotions centers. This study consists of 60 respondents.which are the Bumiputera wood-based companies operating in peninsular Malaysia. The primary data was gathered using a set of questionnaires to get the feedback from customers on PUB and its' promotion activities. The objective of this study is to evaluate the effectiveness of PUB's current marketing strategies in promoting Bumiputera Wood-Based Industry, to identify MTIB's successfulness in encouraging the participation of bumiputera companies in the marketing activities carried out by PUB, to find out the awareness of PUB's marketing activities among their client, Bumiputera Wood-Based Companies and finally to find out appropriate strategies that can be taken in promoting the BWB products. According to the data analysis and interpretation done from this study, several findings was obtained. It is obvious that PUB has made a strong presence in assisting the Bumiputera wood-based industry. Besides the promotional activities carried out, Bumiputera's turn to PUB for government and financial support as most of these companies do not have enough financial capacity to do their own promotion or to upsize their company. It is also found that there are certain ways that the PUB can help increase their efficiency in assisting the Bumiputera such as to do research and design and quality control for these products so that it will meet international standards. Malaysia has the skill to produce beautifully carved furniture and using high quality of woods but more promotions should be done especially attract the international market.